PENGARUH BIAYA PENDIDIKAN DAN BIAYA PROMOSI TERHADAP PENINGKATAN JUMLAH MAHASISWA DI STMIK PPKIA PRADNYA PARAMITA MALANG - MAKNUNAH, JAUHARUL (DINAMIKA DOTCOM, 2013)
Problems in research on the effects of promotion and education to increase the number of students, the goal is to determine the effect of promotion and education to increase the number of students and the relationship of the simultaneous promotion and education withÂ  the numberÂ  of students.Methods that are used in this research is descriptive and statistical analysis methods multiple linear regression and multiple correlation. promotion costs and the cost of education has not changed so much as an increase in the number of students is 401,462 when the cost of promotion (X1) increased by Rp 100.000,00 be a decline of 1.976, and the cost of education (X2) increased by RpUSD 100,000 , 00 the number of students will increase by 2.236. Correlation results showed that the relationship of these variables is very strong as indicated by the value of R = 0.912 and the coefficient of determination (R square) of 0.831, indicating that the variable increase in the number of students (Y) of 83.1% is affected by the variable cost of promotion (X1) and the variable cost of education (X2), while the remaining 16.9% is explained by other variables. Keywords: Campaign Costs, Tuition Fee, Student